Peningkatan Kapasitas Bisnis Usaha Mikro Kuliner di Sekitar Kampus Universitas Islam Bandung melalui Penyusunan Model Bisnis Hijrah Tool - Sebayang, Asnita Frida; Rahmi, Dewi; Mahani, Septiana Estri Ayu; Al Rifah, Cecep Fauzan (Jurnal SOLMA, 2025)
Background: The campus has a strategic role in enhancing community capacity through the tridharma of higher education, particularly community service. In the context of local economic development, the role of universities is believed to bring changes to the community's economy through the transfer of knowledge and concrete actions. This program aims to improve the competence of culinary business actors in managing their businesses, thereby contributing to long-term welfare improvement. Method: The method used is participatory action research. The community service team conducted an assessment of the needs of micro-business actors in the culinary sector around Universitas Islam Bandung in Tamansari, Bandung City, West Java Province. One of the basic assessments is guiding the actors to recognize and create simple business models after being provided with an understanding of several managerial contexts, including marketing. Results: The results of this program show that business actors can elaborate on 13 business indicators in detail, including strengths, potentials, operational methods, and business development strategies. This program also successfully identified obstacles such as business registration and halal certification, which were assisted by Universitas Islam Bandung. Conclusion: This program is considered successful in enhancing the ability of culinary micro-business actors to develop strategic business models while identifying business development challenges to be addressed. The ability of business actors to create business models is a strategic step to identify business behaviors and will be the key to future business development to become a sustainable source of income by utilizing their resources.